2004
DOI: 10.1021/jp049615z
|View full text |Cite
|
Sign up to set email alerts
|

The S2 → S1 Internal Conversion of Benzophenone and p-Iodobenzophenone

Abstract: Two modes of excitation (S 0 f S 2 and S 0 f S 1 ) of benzophenone (BP) and p-iodobenzophenone (p-IBP) in acetonitrile have been examined by ultrafast pump-probe experiments. The S 1 states (λ max ∼ 575-580 nm) of BP and p-IBP were observed to be generated with lifetimes of 0.53 and 0.59 ps, respectively, following excitation at 267 nm, and this has been attributed to the S 2 f S 1 internal conversion. The rates of the S 1 f T 1 ISC have been observed to be similar following either 267 or 335 nm excitation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
51
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 29 publications
11
51
0
Order By: Relevance
“…9(b) renders a first exponential time constant of 1.0 ps and a second one of 6.3 ps. Due to the 310 nm excitation, there is a first ultrafast S 2 →S 1 relaxation [38], the intersystem crossing seems to be accelerated both by water as solvent and the S 2 excitation from the typical 10 ps [37,39].…”
Section: Improved Spectroscopic Resultsmentioning
confidence: 99%
“…9(b) renders a first exponential time constant of 1.0 ps and a second one of 6.3 ps. Due to the 310 nm excitation, there is a first ultrafast S 2 →S 1 relaxation [38], the intersystem crossing seems to be accelerated both by water as solvent and the S 2 excitation from the typical 10 ps [37,39].…”
Section: Improved Spectroscopic Resultsmentioning
confidence: 99%
“…The short growth time is due to the ultrafast internal conversion (IC) of S n directly to S 1 (S 1 also has an absorption contribution at 505 nm) and the higher value results from the S 1 →T 1 transition. The S 1 →T 1 transition time of ≈6 ps is shorter than the ≈10 ps observed for BP38 and this indicates that the presence of nitrogen in the aromatic ring accelerates the ISC rate of the 2‐BPy molecule. Considering the remarkable differences in the polarity and hydrogen‐bonding ability of MeCN and water, the similarity of the spectra and dynamics of the two solvent systems suggests there is only a modest influence of these solvent properties on these processes.…”
Section: Resultsmentioning
confidence: 75%
“…Inspection of Figure 3 shows that the spectra acquired in neat MeCN (A) and in neutral aqueous solvent (B) are similar at short delay times as a broad absorption ( λ max =560 nm) was observed that can be assigned to the S 1 →S n transition 24. 38 The initial changes in the spectra have mainly been attributed to S 1 →T 1 intersystem crossing (ISC), which results in the well‐known absorption corresponding to the T 1 →T n transition with a maximum at 505 nm. The formation of the T 1 states was monitored at 505 nm and the results are displayed in Figure 4 together with exponential fittings of the experimental data points.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, the properties and reaction mechanisms of the ketyl radical and the radical from the solvent and their reaction to produce a light absorbing transient (LAT) have been reported . The intersystem crossing from S 1 to T 1 for BP and its derivatives has been observed directly by ultrafast TA with measured rates of ~10 11 s –1 , and a rapid water addition process to the protonated BP triplet was identified to result in the fast deactivation of the triplet BP in acidic aqueous solution . Moreover, nanosecond time‐resolved resonance Raman (ns‐TR 3 ) spectroscopy is an effective technique for further clearly characterizing the structural and electronic properties of transient species, and has been used to help identify the intermediates and photoproducts of BP and its derivatives .…”
Section: Introductionmentioning
confidence: 99%